The Assessment of Accredited Faculties Performance at Assiut University by Using Balanced Scorecard (BSC) - Bahaaaldeen Arabi Mohamad Mohamad (European Scientific Journal, ESJ, 2016)
The current study aimed at recognizing the concept and aims of performance evaluation besides to shedding light on balanced Scorecard as it is considered one of the modern models in performance assessment and evaluation. The study aimed at assessing the performance of accredited faculties at Assiut University by using this scorecard. The researcher used the descriptive method as it suits the study nature. The study sample consisted of 20% percentage of the original society of the study from staff members and with 5% percentage of the original society of study from students.it was selected in a random way. The current study came down to some important results related to the theoretical framework and the field study:(1)the balance scorecard is considered one of the modern tools and the most effective tool in measuring and assessing the balanced performance because it gathers among the financial and non-financial tools, besides to that, it gathers the quantitative and specific values in addition to the external and internal factors on the short and long term.(2)the performance related to the internal process efficiency came at a medium degree at all the performance was weak, while the performance was medium at the total of the sample size. The researcher ended his study with setting some important recommendations to implement this technique in an effective way.